2015
DOI: 10.1111/neup.12227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative integrated molecular analysis of intraocular medulloepitheliomas and central nervous system embryonal tumors with multilayered rosettes confirms that they are distinct nosologic entities

Abstract: Intraocular medulloepithelioma (IO MEPL) is an uncommon embryonal neuroepithelial neoplasm of the eye. These ocular neoplasms have been compared with intracranial medulloepitheliomas or other histologic variants of CNS embryonal tumor with multilayered rosettes (CNS ETMR) due to their morphological mimicry. We performed comprehensive molecular analysis to explore the histogenetic and biologic relationships between 22 IO MEPL and 68 CNS ETMR. Routinely prepared paraffin-embedded samples were assessed for genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…In two large series, Korshunov et al [13] have recently proved that intraocular medulloepitheliomas and embryonal tumors of the central nervous system with multilayered rosettes are distinct nosologic entities, and Sahm et al [14] found a high prevalence of DICER1 and KMT2D somatic mutations. Both the punch and FNA biopsies of our tumor showed trisomy of chromosome 3, which was rare in those series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two large series, Korshunov et al [13] have recently proved that intraocular medulloepitheliomas and embryonal tumors of the central nervous system with multilayered rosettes are distinct nosologic entities, and Sahm et al [14] found a high prevalence of DICER1 and KMT2D somatic mutations. Both the punch and FNA biopsies of our tumor showed trisomy of chromosome 3, which was rare in those series.…”
Section: Discussionmentioning
confidence: 99%
“…The cytogenetics of medulloepithelioma are only recently beginning to be elucidated, with many genetic alterations including abnormalities in chromosomes 1, 4, 6, 8, 15, and 16 [11,12,13]. In two large series, Korshunov et al [13] have recently proved that intraocular medulloepitheliomas and embryonal tumors of the central nervous system with multilayered rosettes are distinct nosologic entities, and Sahm et al [14] found a high prevalence of DICER1 and KMT2D somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar tumor is found in the brain but has different genetic and epigenetic findings [2,3,4,5]. For every 100-150 retinoblastomas 1 ocular medulloepithelioma may occur.…”
Section: Introductionmentioning
confidence: 97%
“…The cerebral medulloepithelioma is often large at diagnosis and is by definition classified as a high-grade malignant tumor although long-term survivors have been described. Only recently has the demonstration of molecular diversity at the cytogenetic and epigenetic levels enabled the identification of brain and ocular medulloepithelioma as separate nosologic entities [5,6]. Strict separation between a benign and malignant variant of intraocular medulloepithelioma does not reflect the clinical behavior of these tumors for as far as it can be deduced from small case series and case reports [7,8].…”
Section: Tablementioning
confidence: 99%
“…This notion is supported by the recently published molecular data on intraocular medulloepithelioma, which showed clustering in the same part of the dendrogram tree using unsupervised cluster analysis. There were no additional subclusters within the intraocular medulloepithelioma cohort separating histologically malignant from nonmalignant cases [6]. Neither could single nucleotide polymorphism array detect differences in copy number aberrations between benign and malignant medulloepithelioma.…”
Section: Tablementioning
confidence: 99%